Intersecting cultural identities and help-seeking attitudes: the role of religious commitment, gender, and self-stigma of seeking help. Issue 6 (3rd July 2018) - Brenner, Rachel E.; Engel, Kelsey E.; Vogel, David L.; Tucker, Jeritt R.; Yamawaki, Niwako; Lannin, Daniel G.
ABSTRACT: The current study ( N  = 404) used a moderated moderation model to examine how gender, religious commitment, and self-stigma toward seeking psychological help may interact in the prediction of help-seeking attitudes. Bivariate zero-order correlations indicated that help-seeking attitudes was negatively associated with self-stigma of seeking help ( r  = −.55) and positively associated with religious commitment ( r  = .14), and self-stigma was not significantly associated with religious commitment. Men reported more negative attitudes than women (Δ M  = −.18). Furthermore, multiple regression results revealed a three-way interaction such that the relationship between gender and help-seeking attitudes was moderated by both self-stigma and religious commitment. Specifically, men with high religious commitment and high self-stigma endorsed the most negative help-seeking attitudes, suggesting that religious men's help-seeking attitudes may be particularly susceptible to the influence of self-stigma. Implications for research and the development of targeted interventions are discussed.